Effects of a Multi-Session Cognitive Training Combined With Brain Stimulation (TrainStim-Cog) on Age-Associated Cognitive Decline – Study Protocol for a Randomized Controlled Phase IIb (Monocenter) Trial - Antonenko, Daria; Thams, Friederike; Uhrich, Jessica; Dix, Annika; Thurm, Franka; Li, Shu-Chen; Grittner, Ulrike; Flöel, Agnes (Frontiers in Aging Neuroscience, 2019)
Background: With increasing aging populations worldwide, developing interventions against age-associated cognitive decline is particularly important. Evidence suggests that combination of brain stimulation with cognitive training intervention may enhance training effects in terms of performance gain or transfer to untrained domains. This protocol describes a Phase IIb clinical trial that investigates the intervention effects of training combined with brain stimulation in older adults. Methods: The TrainStim study is a monocentric, randomized, single-blind, placebo-controlled intervention. The study will investigate cognitive training with concurrent anodal tDCS (transcranial direct current stimulation) over the left dorsolateral prefrontal cortex (target intervention) compared to cognitive training with sham stimulation (control intervention) over nine sessions in three weeks, consisting of a letter updating task and a three-stage Markov decision-making task. Fifty-six older adults will be recruited from the general population. Baseline assessment will be performed including neuropsychological screening and performance on training tasks. Participants will be allocated to one of the two study arms using block-wise randomization stratified by age and baseline performance with a 1:1 allocation ratio. Primary outcome is performance in the letter updating task after training under anodal tDCS compared to sham stimulation. Secondary outcomes include performance changes in the decision-making task and transfer tasks, as well as brain structure and functional networks assessed by structural and functional magnetic resonance imaging that are acquired pre- and post-intervention. Significance: The main aim of the TrainStim study is to provide evidence for behavioral and neuronal effects of tDCS-accompanied cognitive training and to elucidate the underlying mechanisms in older adults. Our findings will contribute towards developing efficient interventions for age-associated cognitive decline. Trial registration: This trial was retrospectively registered at ClinicalTrials.gov with the Identifier: NCT03838211 at February 12, 2019. https://clinicaltrials.gov/ct2/show/NCT03838211 Protocol version: Based on BB 004/18 version 1.2 (May, 17, 2019).